The determinants of capital structure : plantation industry - Nurul Ain, Rozman (2017)
This research investigates the relationship between capital structure and firms’ performances. The sample of this study are based on Malaysia plantation companies from year 2010 to 2014 to analyze the most optimum capital structure. This study uses leverage (LEV) as the dependent variable against seven independent variables which are firm size (SIZE), growth (GROWTH), asset structure (ASTRUCT), business risk (RISK), liquidity (LIQUID), tax shield (TAX) and profitability (PROFIT) in determining the firms’ financial performances. The sample of this study comprises 35 listed companies in Bursa Malaysia with 6 companies are excluded due to insufficient of data. In this paper, asset structure, firm size and tax shield found to be in line with the trade-off theory with positive relationship with leverage. Meanwhile, the profitability follows the pecking order theory with negative correlation with leverage. Business risk, growth and liquidity does not influence the capital structure of Malaysia plantation firms.